A inserção da noção de competências em cursos de graduação em Administração: O Discurso e a Prática em Instituições de Educação Superior Localizadas em Belo Horizonte; Minas Gerais - Simone Costa Nunes (2007)
Recent proposals for change in national education, in keeping with International tendencies in Education in the XXI Century have been incorporating the notion of competencies as the curricular organization and pedagogical projet guide at all levels of education in the conuntry.Bearing this scenario in mind, a study regarding the insertion of that Notion in undergraduate Administration courses has been proposed with the intent of contributing thought regarding the construction of competencies in higher education. It deals with qualitative research based on multiple case studies in 12 institutions of higher Educationlocated in Belo Horizonte, Minas Gerais. The results point out that there is a tendency to adopt a model of transmission of knowledge in detriment of the construction of competencies. Beside this, a proposal for articulating competencies through the practice of teaching was not evidenced. In this sense, Pedagogy does not direct the courses under study, there not having been observed a systematized and articulate direction among all the elements making up the teaching and learning process.